Pelaksanaan Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah Terhadap Peningkatan Pendapatan Asli Daerah Di Kota Langsa - Safrizal Wahyudi; Muhammad Abduh; Faisal Akbar; Jusmadi Sikumbang (USU LAW JOURNAL, 2019)
Abstract. The regional authority in collecting taxes and levies is regulated by Law No. 28 of 2009 concerning Regional Taxes and Regional Levies. Based on this law, regions are given the authority to collect 11 types of taxes and 33 types of user fees, with the consideration that these types of taxes and user charges are generally good. This research is used normative legal research method. Normative legal research is research by only processing and using secondary data relating to the issue of "Implementation of the Regional Parliamentary Oversight Function Against Increasing Local Revenue in Langsa City". The type of research used is normative juridical, then the approach taken is the statute approach. The DPRD in general, especially the Langsa City DPRD in carrying out its supervisory function, is expected to truly be able to ensure that the regional government is in the public interest, and must be able to realize the shared goals and interests agreed in the legislation and budgeting process. The aspirations of the community are essentially institutionalized through their representatives in the DPRD, especially in the field of supervision.   Keywords: supervision, enhancement, locally genereted revenue